Application of DV-SIA manifold for determination of thiocyanate ions in human saliva samples - Acebal, Carolina Cecilia (2012)
An automated, simple and inexpensive double-valve sequential injection analysis (DV-SIA) spectrophotometic method with online liquid-liquid extraction, for the determination of thiocyanate has been developed. The method has been based on the formation of an ion associate between thiocyanate and Astra Phloxine in acidic medium, and the subsequent extraction with amylacetate. The absorbance of the extracted ion associate was measured at 550 nm. The calibration function was linear in the range 0.05-0.50 mmol L-1 and the regression equation was A = (1.887 ± 0.053) [SCN- mmol L-1] + (0.037 ± 0.014) with a correlation coefficient of 0.995. The precision of the proposed method was evaluated by the relative standard deviation (RSD) values at two concentration levels: 0.20 and 0.50 mmol L-1. The obtained results were 1.0 and 2.8%, respectively, for the intra-day precision, and 4.2 and 3.8%, respectively for the inter-day precision. The calculated detection limit was 0.02 mmol L-1. The developed method has been successfully applied for determining thiocyanate ions in human saliva samples. © 2012 Elsevier B.V. All rights reserved.